The Effect of Ethnomathematics Approach on Numbers 1-20 Counting Skills for Children 4-6 Years Old - Siregar, Sakinah; Lubis, A. Naashir M. Tuah (Jurnal Pendidikan Anak, 2024)
Children aged 0-6 years are at an age where cognitive development is very rapid. Counting ability is one of the things that cannot be ignored in this case. The Ethnomathematics approach is an approach that prioritises cultures that contain mathematical values This study aims to determine the ethnomathematics approach to counting skills 1- 20 students aged 4-6 years. This research is a quasi-experimental research with posttest only control design, with a sample of 22 children out of 44 students at RA Al-Qur'an Dina Padang Matinggi. The results showed a significant effect of initial counting ability on the final counting ability of experimental class students using the ethnomathematics approach.experimental class students who used the ethnomathematics approach. Statistical results show the value of F = 18,861 with a significance of 0.000 (p < 0.05). The Ethnomathematics approach can be used in the learning process at the early childhood education level. So that counting skills can develop through this approach. And of course it is necessary to pay attention to the understanding of the culture possessed by students after the learning process is carried out